Student perspectives on health dialogues: how do they benefit? - Rising Holmström, Malin (Int J Qual Stud Health Well-being, 2021)
The vast majority of students in Sweden are healthy and live good lives, but rising health problems and declining academic performance pose risks to the country’s student population. School health services (SHS) in Sweden have a long tradition of hosting health dialogues (HD) with students to support their health and its repercussions on their learning. Purpose: To describe experiences from 6- to 16-year-old students participating in the health dialogue in school. Method: Descriptive qualitative design. Data were collected from 734 open-ended responses on a questionnaire distributed among students ranging in age from 6 to 16. The data were subjected to qualitative content analysis. Findings: The analysis identified five categories: Important to identify health and health problems, School nurse, a key profession, School environment important for both health and learning, Importance of health screening and Important to have a healthy lifestyle. The findings revealed that students aged 6 to 16 years old consider health and health problems, school environment, health screening and healthy lifestyle to be important areas for health and learning School nurses were identified as key persons in HD and for student’s experience of health and learning. Conclusion: HD is an opportunity for students to participate and influence decisions concerning their health and education, to actively engage in their own health and learning in areas that affect them for example, the school environment.